Sex‐related differences in behavioral and amygdalar responses to compound facial threat cues. Issue 7 (8th March 2018) - Im, Hee Yeon; Adams, Reginald B.; Cushing, Cody A.; Boshyan, Jasmine; Ward, Noreen; Kveraga, Kestutis
Abstract: During face perception, we integrate facial expression and eye gaze to take advantage of their shared signals. For example, fear with averted gaze provides a congruent avoidance cue, signaling both threat presence and its location, whereas fear with direct gaze sends an incongruent cue, leaving threat location ambiguous. It has been proposed that the processing of different combinations of threat cues is mediated by dual processing routes: reflexive processing via magnocellular (M) pathway and reflective processing via parvocellular (P) pathway. Because growing evidence has identified a variety of sex differences in emotional perception, here we also investigated how M and P processing of fear and eye gaze might be modulated by observer's sex, focusing on the amygdala, a structure important to threat perception and affective appraisal. We adjusted luminance and color of face stimuli to selectively engage M or P processing and asked observers to identify emotion of the face. Female observers showed more accurate behavioral responses to faces with averted gaze and greater left amygdala reactivity both to fearful and neutral faces. Conversely, males showed greater right amygdala activation only for M‐biased averted‐gaze fear faces. In addition to functional reactivity differences, females had proportionately greater bilateral amygdala volumes, which positively correlated with behavioral accuracy for M‐biased fear. Conversely, in males only the right amygdala volume was positively correlated with accuracy for M‐biased fear faces. Our findings suggest that M and P processing of facial threat cues is modulated by functional and structural differences in the amygdalae associated with observer's sex.